The Importance of Excising or Suturing the Posterior Mucosal Flaps in External Dacryocystorhinostomy - , Muhammad Fayyaz, Faisal Aziz Khan, Muhammad Amer Yaqub (Pakistan Journal of Ophthalmology, 2010)
Purpose: To compare the success rate of external dacryocystorhinostomy (with intubation) with suturing of the posterior flaps and without suturing of the posterior flaps. Material and methods: A prospective comparative study of 70 patients attending the Ophthalmology Department Military Hospital Rawalpindi between Dec 2005 and March 2007 who underwent external DCR after dividing them into two groups of 35 each. In one group posterior flaps were sutured and in the other group posterior flaps were excised. All external DCRs were performed under general anesthesia. The posterior flaps were sutured with 5/0 vicryl or excised with spring scissors. All DCRs were intubated. The tube was removed after 03 months. At 04 months, the success was judged if there was relief of epiphora and potency confirmed by probing syringing. Results: The success rate was 97.1% in DCR with suturing of the posterior flaps and 94.3% in DCR with excision of posterior flaps. Statistically the difference in results were insignificant. (P-value > 0.05). Conclusion: The surgical success of DCR with suturing of the posterior flaps is statistically insignificant to DCR without suturing of the posterior flaps.